Ketahanan Beberapa Jamur Patogen terhadap Fungisida - Christanti Sumardiyono; Nursamsi Pusposendjojo; Sri Trisnowati (Jurnal Perlindungan Tanaman Indonesia, 1995)
Chemical control of plant pathogens have been done for a long time using contact and systemic fungicides. Resistance of the pathogens to fungicides may caused failure of disease control program. Studies by in vitro, in green house and fields were done at Yogyakarta to know the fungal which were resistant to several fungicides after treatment. The pathogen tested to fungicides were Colletotrichum capsici on red pepper to propineb, mancozeb, mixture of carbendazim and mancozeb, and thiophanate methyl, Alternaria porri on garlic to thiophanate methyl, Phytophthora palmivora on cocoa to Al-fosetyl, metalaxyl, mancozeb, and Copper Oxychloride, and Peronosclerospora maydis on corn to metalaxyl. The study indicated that C. capsici was resistant to propineb, mancozeb, and mixture of carbendazim and mancozeb, but sensitive to thiophanate methyl. A. porri from plant treated with thiophanate methyl indicated resistant to the fungicides. ED50 of Al-fosetyl and metalaxyl on P. palmivora were higher than on mancozeb and copper oxychloride, so that it was resistance strain.